Accuracy of several maternal seric markers for predicting histological chorioamnionitis after preterm premature rupture of membranes: a prospective and multicentric study. (October 2016) - Caloone, Jonathan; Rabilloud, Muriel; Boutitie, Florent; Traverse-Glehen, Alexandra; Allias-Montmayeur, Fabienne; Denis, Laure; Boisson-Gaudin, Catherine; Hot, Isabelle Jaisson; Guerre, Pascale; Cortet, Marion; Huissoud, Cyril; ,
Abstract: Objective: To assess and compare several maternal seric markers for the prediction of histological chorioamnionitis (HCA) after preterm premature rupture of membranes (PPROM). Study design A prospective and multicentric observational study was undertaken, including six French tertiary referral centres. Pregnant women over 18 years, with PPROM between 22 + 0 and 36 + 6 WG were enrolled. A blood sample was obtained before delivery and analysed for C-Reactive Protein (CRP), InterCellular Adhesion Molecule-1 (ICAM-1), Interleukin-6 (IL-6), Interleukin-8 (IL-8), Matrix-Metalloproteinase 8 and 9 (MMP-8, MMP-9), Triggering receptor on myeloid cells (TREM-1), and Human Neutrophile Peptides (HNP). HCA was determined by histological examination distinguishing maternal from fetal inflammatory response. Placental analyses and biological assays were performed in duplicate. Comparison of maternal seric markers levels in women with or vs. without HCA was performed, using a non-parametric Receiver Operating Characteristic. Results: 295 women were kept for analysis. The prevalence of HCA was 42.7% (126/295). The concentrations of MMP-8, MMP-9, HNP and CRP were higher in HCA vs. the non-HCA group ( P  < 0.05) whereas the concentrations of ICAM- 1, IL-6, IL-8 were not different ( P  > 0.05). The ROC curve with the largest AUC was for CRP (AUC; 0.70; 95% CI; 0.64–0.77) and it was significantly higher than those for MMP-8, MMP-9, or HNP ( P  < 0.03). Conclusion: CRP was the best maternal marker for predicting HCA in women with PPROM.